Comparison between two techniques for estimating voluntary intake of female buffaloes under grazing conditions. Technical note - Gutiérrez, Odilia; Cairo, Juan; Ramírez, B.; Vasallo, G.; Valera, M. (Cuban Journal of Agricultural Science, 2016)
In order to compare two techniques for estimating dry matter intake of female buffaloes under grazing conditions, 25 pairs of data were used, obtained from the application of the technique of double marking (Cr2O3 and IAA) and estimation by the method of metabolizable energy. The analysis of variance for a probability level of 95.0% indicated that there were no differences between the intakes estimated by the methods of double marking (17.20 kg DM/d) and energy (16.84 kg DM/d). There was a high correspondence between the DM intakes estimated by both methods, with determination (R2 = 0.94) and correlation coefficient (r = 0.97), and low values of the mean square error. The results demonstrate that the methodology for estimating intake under grazing conditions, proposed by NRC (2001) and adapted by Pérez Infante (2013), can be compared with the traditional technique of double marking, which may be useful for further studies on intake under grazing conditions, destined to buffaloes. Key words: ingestion, grasses, markers